Performance slumps in sport: A systematic review. (July 2022) - Stead, Joe; Poolton, Jamie; Alder, David
Abstract: This systematic review explored the under-researched experience of performance slumps in sport with four objectives: (i) review definitions of a performance slump; (ii) identify known causes of a performance slump; (iii) identify the symptoms athletes present when in a performance slump; and (iv) review approaches used to combat a slump in performance. Literature searches into three databases (PsychARTICLES, PsychINFO and SPORTDiscus) resulted in the inclusion of quantitative ( n = 14) and qualitative ( n = 4) empirical research studies. The findings were thematically analysed and narratively synthesised. Results showed that: (i) definitions of a performance slump vary; (ii) perceived expectations for success and athletes attributing poor performance to something about themselves have been empirically verified as performance slump causes; (iii) during a slump, athletes might display a range of emotional and psychological symptoms and/or adopt skill-focused attention; and (iv) athletes reported several ways of coping with a performance slump, and research has offered succeeding under pressure as a potential route out of a slump. This systematic review highlights the need for an empirical investigation of the performance slump phenomenon. Future studies should be directed towards understanding the prominent symptoms athletes experience during the slump, so that cause, context, competitor and symptomatic dependant intervention strategies can be designed. Highlights: This is the first systematic review conducted on performance slumps in sport. Researchers have classified performance slumps in a variety of different ways. Performance slump causes include: perceived expectations for success and athletes attributing performance decline to something about themselves. Athletes in a slump might display a range of emotional and psychological symptoms and/or adopt skill-focused attention. Several ways of coping with a performance slump have been identified, and research has offered succeeding under pressure as a potential route out of a slump.